Fruitless effort? The effects of risk management disclosure specificity on nonprofessional investors’ judgments - Xinyan Miao; Shaofei Wang; Yue Wang; Bo Zhou (China Journal of Accounting Research)
The widespread use of boilerplate disclosures in financial reporting has led regulators to express concerns about the decision-usefulness of annual reports. We conduct two experiments to determine the effects of risk management disclosure presence and specificity on nonprofessional investors’ judgments. In Experiment 1, we manipulate risk management disclosure at three levels (non-disclosure vs. generic or specific risk management disclosures). Relative to the non-disclosure condition, nonprofessional investors exhibit more favorable investment judgments when provided with a specific risk management disclosure. However, generic disclosure has a negligible influence on nonprofessional investors’ judgments. We find no convincing evidence supporting potential alternative explanations. Experiment 2 confirms this mechanism and provides further evidence that the observed effects are not driven by the lengths of specific disclosures.